2009
DOI: 10.1212/wnl.0b013e3181b6bbe3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a CYP2D6 polymorphism on the efficacy of donepezil in patients with Alzheimer disease

Abstract: The single nucleotide polymorphism rs1080985 in the CYP2D6 gene may influence the clinical efficacy of donepezil in patients with mild to moderate Alzheimer disease (AD). The analysis of CYP2D6 genotypes may be useful in identifying subgroups of patients with AD who have different clinical responses to donepezil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 35 publications
4
61
0
1
Order By: Relevance
“…Patients were treated for 3 months, and response to the treatment was defined conservatively according to the NICE criteria as patients who show improvement or no deterioration in cognition and improvement in functional status (The National Health Service Constitution). The genotypes were correlated with the drug levels according to MMSE classification and according to the genotypes (0, 1, or 2 mutant alleles) [4,28]. In this study, a large interindividual variability in the C/D ratio of donepezil monotherapy was observed, and this variability was significantly correlated with the CYP3A4 genotypes for patients on donepezil monotherapy.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Patients were treated for 3 months, and response to the treatment was defined conservatively according to the NICE criteria as patients who show improvement or no deterioration in cognition and improvement in functional status (The National Health Service Constitution). The genotypes were correlated with the drug levels according to MMSE classification and according to the genotypes (0, 1, or 2 mutant alleles) [4,28]. In this study, a large interindividual variability in the C/D ratio of donepezil monotherapy was observed, and this variability was significantly correlated with the CYP3A4 genotypes for patients on donepezil monotherapy.…”
Section: Discussionmentioning
confidence: 69%
“…Donepezil is metabolized mainly by the cytochrome p450 enzymes CYP2D6 and 3A [2]. However, some studies have reported an impact of CYP polymorphisms on the drug levels in patients on donepezil monotherapy [3,4,5]. So far, no studies have found a correlation between relevant CYP2D6 and CYP3A4 genotypes in patients undergoing donepezil combination therapy and drug levels and clinical response.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the same scales were applied to assess responsiveness to treatment in particular studies, the definitions for treatment response were different. Some studies defined responders as those who obtained the same or higher MMSE scores after a defined period of treatment [16,17]. Raschetti et al [18] defined response to treatment as an increase of at least 2 points in the MMSE after 9 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2D6 was closely associated with the dopamine transporter and rat brain-specific CYP2D18 has been implicated in dopamine metabolism (119). Pilotto et al (120) demonstrated that, in patients with mild to moderate AD, SNP rs1080985 in CYP2D6 may influence the clinical efficacy of donepezil. Whereas, Liu et al (121) found no significant association between rs1080985 SNP in CYP2D6 and common APOE polymorphisms in a Chinese population.…”
Section: Cytochrome P450 Family 2 Subfamily D Member 6 (Cyp2d6)mentioning
confidence: 99%